2014
DOI: 10.1094/mpmi-05-14-0155-r
|View full text |Cite
|
Sign up to set email alerts
|

Potato virus Y HCPro Localization at Distinct, Dynamically Related and Environment-Influenced Structures in the Cell Cytoplasm

Abstract: Potyvirus HCPro is a multifunctional protein that, among other functions, interferes with antiviral defenses in plants and mediates viral transmission by aphid vectors. We have visualized in vivo the subcellular distribution and dynamics of HCPro from Potato virus Y and its homodimers, using green, yellow, and red fluorescent protein tags or their split parts, while assessing their biological activities. Confocal microscopy revealed a pattern of even distribution of fluorescence throughout the cytoplasm, commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Previous studies indicated that potyviral HC-Pros were distributed to the cytoplasm (Riedel et al, 1998;Mlotshwa et al, 2002;Zheng et al, 2011;Sahana et al, 2014), nucleus (Riedel et al, 1998;Sahana et al, 2014), cytoplasm filaments, cell membrane, or nuclear envelope (Zheng et al, 2011). In addition, Turnip mosaic virus HC-Pro and Potato virus Y (PVY) HC-Pro could form aggregates in the cytoplasm (Zheng et al, 2011;del Toro et al, 2014), and an amino acid change of Papaya ringspot virus HC-Pro also led to the formation of the aggregates (Sahana et al, 2014). Interestingly, PVY HC-Pro also could be present in the chloroplasts of PVY-infected plants (Gunasinghe and Berger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that potyviral HC-Pros were distributed to the cytoplasm (Riedel et al, 1998;Mlotshwa et al, 2002;Zheng et al, 2011;Sahana et al, 2014), nucleus (Riedel et al, 1998;Sahana et al, 2014), cytoplasm filaments, cell membrane, or nuclear envelope (Zheng et al, 2011). In addition, Turnip mosaic virus HC-Pro and Potato virus Y (PVY) HC-Pro could form aggregates in the cytoplasm (Zheng et al, 2011;del Toro et al, 2014), and an amino acid change of Papaya ringspot virus HC-Pro also led to the formation of the aggregates (Sahana et al, 2014). Interestingly, PVY HC-Pro also could be present in the chloroplasts of PVY-infected plants (Gunasinghe and Berger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…benthamiana [ 23 ] expressing an inverted repeat fragment of its RNA-dependent RNA polymerase 6 (RDR6 ) gene that reduced the levels of the endogenous transcript mRNA to 4% of that found in non-silenced plants was also used, kindly provided by Prof. D. C. Baulcombe (University of Cambridge, UK). Viruses: we used an aphid transmissible PVY isolate (Scottish ordinary variety PVY-O, Scottish Agricultural Science Agency) from which the P1-6x-HCPro sequence contained in the binary constructs P1-6x-HCPro and PVX-P1-6x-HCPro [ 24 , 25 ], respectively, and described below derive. We used a cloned CMV isolate, strain Fny, obtained by inoculating combined in vitro transcripts of full-length infectious clones of viral RNAs 1, 2, and 3 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most recent and thorough examination of subcellular localization comes from a study performed by del Toro et al . () with the PVY HCPro fused to diverse fluorophores. In addition to a diffuse presence of this viral protein in the cytoplasm, they also observed distinct protein distributions (e.g.…”
Section: Structure Versus Function—hcpro Is a Multidomain Viral Proteinmentioning
confidence: 99%